Knowledge, awareness, and attitude of medical students concerning genetics and premarital screening - Syed Sameer Aga; Yara Abdulaziz Alghamdi; Amal Abdullah Alghamdi; Muhammad Anwar Khan (Wolters Kluwer Medknow Publications, 2021)
Objectives: The objectives of the study are to evaluate the medical students' knowledge, awareness, and attitude of genetics and genetic testing in general and premarital screening (PMS) in particular. Materials and Methods: An online predesigned, validated, and self-administered questionnaire was dispensed to all medical students of our university. This included questions regarding sociodemographic data, genetics, genetic testing, and PMS. Results: A total of 302 students responded to the survey with a mean age of 21.68 ± 2.32 (standard deviation) of which 38.7% were males and 61.3% were females. 51 (16.9%) students were from Phase I, 124 (41.1%) from Phase II, 127 (42.1%) from Phase III of College of Medicine KSAU-HS, Jeddah Campus. 224 (74.2%) of the participants had no direct relationship between the parents and 23 (7.6%) had personal history of hereditary disease. About 86.1% of students knew that genetic counseling is available in the Kingdom and 83.4% were familiar with PMS. Majority of students (female = 83.2%; male = 84.6%) did perceive that consanguinity can increase the chance of hereditary diseases. Overwhelming majority (female = 94.1%; male = 85.4%) agreed to make PMS obligatory before marriage, 87.4% of which were Phase III students. However, only a minority of students disagreed with marriage to be allowed even if the result of PMS came incompatible and most agreed to carrying out PMS which contrasts what others have reported. Conclusions: Majority of students had a positive attitude toward PMS, much higher than previously reported, thereby reflecting upon the importance of medical education as a lynchpin between the knowledge and practice.